High Energy Density Physics Research Using Intense Heavy Ion Beam at FAIR: The HEDgeHOB Program. (March 2016) - Tahir, N.A.; Shutov, A.; Piriz, A.R.; Deutsch, C.; Stöhlker, Th.
Abstract: International project, Facility for Antiprotons and Ion Research (FAIR), has entered in its construction phase at Darmstadt. It is expected that the new powerful heavy ion synchrotron, SIS100 will deliver a strongly bunched intense beam of energetic uranium ions that will provide the scientists with an efficient and novel tool to research High Energy Density (HED) Physics in the laboratory. Over the past 15 years, substantial theoretical work has been done to design numerous experiments that can be done at this facility in this field. This work has resulted in an extensive scientific proposal named HEDgeHOB, that includes experiment proposals addressing various aspects of HED matter, for example, planetary physics, equation of state, hydrodynamic instabilities and others. In this paper we present a summary of this work.